2011
DOI: 10.1111/j.1742-4658.2011.08385.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and verification of heat shock protein 60 as a potential serum marker for colorectal cancer

Abstract: Colorectal cancer (CRC) is a major public health issue worldwide, and novel tumor markers may contribute to its efficient management by helping in early detection, prognosis or surveillance of disease. The aim of our study was to identify new serum biomarkers for CRC, and we followed a phased biomarker discovery and validation process to obtain an accurate preliminary assessment of potential clinical utility. We compared colonic tumors and matched normal tissue from 15 CRC patients, using two-dimensional diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
58
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 46 publications
(89 reference statements)
8
58
0
Order By: Relevance
“…Various data support the hypothesis that Hsp60 favors carcinogenesis and show a close correlation between high levels of Hsp60 and different types of cancer, thus the immunopositivity for Hsp60 can be considered a biomarker useful for the diagnosis and monitoring these types of malignancies [33,[49][50]. Frequently, the immunopositivity for Hsp60, in cancerous tissue or circulating cancer cells, correlates with a poor prognosis [49,[51][52][53].…”
Section: Discussionmentioning
confidence: 95%
“…Various data support the hypothesis that Hsp60 favors carcinogenesis and show a close correlation between high levels of Hsp60 and different types of cancer, thus the immunopositivity for Hsp60 can be considered a biomarker useful for the diagnosis and monitoring these types of malignancies [33,[49][50]. Frequently, the immunopositivity for Hsp60, in cancerous tissue or circulating cancer cells, correlates with a poor prognosis [49,[51][52][53].…”
Section: Discussionmentioning
confidence: 95%
“…These criteria led us to select aldolase A, cyclophilin A, and annexin A2 as candidates. We did not include HSP60, neutrophil defensin1, or alpha-actinin-1, because previous reports had already suggested that these proteins might be biomarkers for CRC [2629]. …”
Section: Discussionmentioning
confidence: 99%
“…For example, the mitochondrial chaperone HSP60 protects tumor cells from Bax-dependent cell death and CypD-dependent cell death by regulating mitochondrial permeability transition [116, 117]. HSP60 is also positively associated with tumor progression and hormone resistance in prostate cancer [118], and tumor differentiation in colorectal cancer [119]. mtHSP70, or mortalin, promotes tumor cell survival and epithelial-to-mesenchymal transition (EMT) by regulating the activities of p53 and PI3K–Akt pathways [120, 121], as well as facilitating metastasis of breast carcinoma and hepatocellular carcinoma [122, 123].…”
Section: The Uprmt and Cancermentioning
confidence: 99%